Improving Carbon Mitigation Potential through Grassland Ecosystem Restoration under Climatic Change in Northeastern Tibetan Plateau - Lin Huang; Xinliang Xu; Quanqin Shao; Jiyuan Liu (Advances in Meteorology)
To protect the water tower’s ecosystem environment and conserve biodiversity, China has been implementing a huge payment program for ecosystem services in the three rivers source region. We explored here the dynamics of grassland degradation and restoration from 1990 to 2012 and its relationships with climate mitigation in the TRSR to provide a definite answer as to the forcing and response of grassland degradation and restoration to climate change. Then we estimated its potential of climate mitigation benefits to address the question of whether ecological restoration could be effective in reversing the decline of ecosystem carbon mitigation service. The trend of average annual temperature and precipitation observed by meteorological stations were approximately increased. Compared before and after 2004, the area of grassland degradation was increased slightly. However, nearly one-third of degraded grassland showed improvement, and the grassland vegetation coverage showed significant increase. Comparing current grassland vegetation coverage with healthy vegetation cover with the same grass type, nearly half of the area still needs to further restore vegetation cover. The grassland degradation resulted in significant carbon emissions, but the restoration to its healthy status has been estimated to be technical mitigation potential.